Diversification Strategy and Financial Performance of Nigeria Private Firms - Ozigbo, Ada Mac-; Daniel, Dr. Cross Ogohi (International Journal of Scientific Research and Management (IJSRM), 2020)
The relationship between diversification and firm performance varies among institutions and over time. Less is known about the advantageousness of diversification in economy-wide crises, which have occurred frequently in recent years Using data from a recent survey, we studied nearly 400 Nigeria private firms using two different approaches panel and cross-period comparisons. The findings of both approaches show that diversified firms performed better than focused firms. This was also true during the 2008 global financial crisis. The higher the diversification level, the more positive the firm performance was. We also investigated the influence of ownership structure. Firms that are totally owned by the founding owner and his/her family tend to have unsatisfactory performance under crisis. This finding provides evidence of the increasing attention on management and governance to explain firm. Linear regression models were evaluated to test the effect of diversification on firm performance. Panel A uses profit as the dependent variable, and Panel B uses sales. For each year (2007, 2008, and 2009), two regression models were evaluated: one testing the impact of diversification and the other testing the impact of the diversification level. We found that diversified firms performed better than focused firms during the recent global financial crisis. The diversification level was positively and linearly related to performance, that is, more diversified firms performed better. Moreover, we found that private firms that are totally owned by the founding owner and his/her family performed worse under crisis.